Perioperative diagnosis of euglycaemic ketoacidosis. (February 2016) - Yeow, Chia; Wilson, Frederick; Walter, Edward; Sultan, Javed
Euglycaemic diabetic ketoacidosis is a term describing features of diabetic ketoacidosis but with normoglycaemia. We present a case of a perioperative diagnosis of euglycaemic ketoacidosis in a patient not known to be diabetic, and the subsequent management of the patient. A 65-year-old lady was scheduled for re-exploration of a giant paraoesophageal hernia, which had been initially repaired over six weeks previously. She developed dysphagia soon after the initial surgery and had low caloric intake. Arterial blood gases performed intraoperatively revealed metabolic acidosis with a normal lactate level. It did not respond to intravenous fluid therapy and sodium bicarbonate. Euglycaemic ketoacidosis was confirmed with raised serum ketone level. Insulin and dextrose infusions were commenced and she was managed in intensive care unit where the metabolic acidosis resolved over a 12-h period.